To trust or not to trust? COVID-19 facemasks in China-Europe relations : lessons from France and the United Kingdom - Emilie Tran; Yu-chin Tseng (Journal of Risk and Financial Management, 2022)
At the crossroads of sociology and international relations, this interdisciplinary and comparative research article explores how the COVID-19 outbreak has impacted China-Europe relations. Unfolding the critical moments of the COVID-19 outbreak, this article characterizes the evolution of China-Europe relations with regard to the facemask. This simple object of self-protection against the coronavirus strikingly became a source of contention between peoples and states. In the face of this situation, we argue that the facemask is the prism through which to illustrate (1) the transnational links between China and its overseas population, (2) the changing social perceptions of China and Chinese-looking people in European societies, and (3) the advent of China's health diplomacy and its reception in Europe. Comparing two European settings-France and the United Kingdom (UK)-the common denominator appears to be the reduced trust, if not outright distrust, between individuals and communities in the French and British contexts, and in Sino-French and Sino-British relations at the transnational level. Combining critical juncture theory and (dis)trust in international relations as our analytical framework, this article examines how the facemask became a politicized object, both between states and between Mainland China and its overseas population, as the epidemic unfolded throughout Europe. Adopting a qualitative approach, our dataset comprises the analysis of official speeches and statements; press releases; traditional and social media content (especially through hashtags such as #JeNeSuisPasUnVirus, #IAmNotAVirus, #CoronaRacism, etc.); and interviews with Chinese, French, and British community members.
Keywords: 650; (dis)trust; COVID-19; critical juncture; facemasks; health diplomacy; racism